Crude Polysaccharide Fraction from Rosa rugosa Thunb. Root—Chemical Characterisation, Enzyme Inhibitory, Antioxidant and Antiproliferative Activity - Agnieszka Łubek-Nguyen; Marta Olech; Natalia Nowacka-Jechalke; Aleksandra Martyna; Konrad Kubiński; Maciej Masłyk; Marcin Moczulski; Sebastian Kanak (Applied Sciences, 2022)
Rosa rugosa Thunb. (Rosaceae) plantations can provide industrial amounts of roots, which contain many biologically active metabolites. Here, we report the first studies of the chemical composition and pharmacological potential of a crude polysaccharide fraction obtained from R. rugosa roots (CPL-Rx). It was found that the roots contained water-soluble and -insoluble sugars, including a large amount of β-glucans (12.95 ± 0.30 g/100 g). The water-soluble fraction was found to be mostly composed of sugars (28.94 ± 0.01%), uronic acids (2.61 ± 0.41%), and polyphenols (4.55 ± 0.12%). High-performance capillary electrophoresis analysis showed that glucose was the prevalent monosaccharide (64.31%), followed by a smaller amount of galactose (11.77%), fructose (11.36%), and arabinose (4.27%). SDS-PAGE followed by liquid chromatography mass spectrometry revealed the presence of unbound protein identified as protein plastid transcriptionally active 14-Like. CPL-Rx was found to inhibit the activity of pro-inflammatory enzymes (cyclooxygenase and hyaluronidase) and to have antioxidant potential in the Trolox equivalent antioxidant capacity assay (0.302 ± 0.01 mmol Trolox/g), DPPH radical scavenging effect (EC50 3.92 ± 0.12 mg/mg DPPH•) and oxygen radical absorbance capacity assay (0.134 ± 0.10 mmol Trolox/g). It also exerted a slight antiproliferative effect on SW480 (colon) and A549 (lung) cancer cell lines. Our research provides the first insights into the composition and pharmacological application of crude polysaccharides from rugosa rose roots. It suggests that CPL-Rx may potentially be used for cosmetic and bio-medical purposes, especially as an antihyaluronidase or chemopreventive agent.